The sophists: the philosophy as therap - Ponce Bodino, Hector (2016)
The article covers the steps of classical Greece through the mythology, the pre-Socratic, tragedy and the Sophists to the distinction of natural laws and social laws; distinction that allowed criticize the status quo justified in a natural order.